EFFECT OF STRESS, ANXIETY AND DEPRESSION ON SLEEP QUALITY AMONG UNIVERSITY STUDENTS - Chakerwarti, Payal; Singh, Divyanshi (International Journal of Psychosocial Rehabilitation, 2025)
Sleep is a basic human need. Abraham Maslow showed that sleep as part of your physiological needs in the hierarchy of five basic human needs. According to Stores, sleep categorized into: satisfactory and unsatisfactory. Good sleep is sleep that has satisfactory (sufficient in duration and good quality), while bad sleep is sleep that makes individuals feel unsatisfactory. Unsatisfactory sleep that occurs on a continued that cause × more serious effects like; often feel very tired, uncontrolled emotion, difficult to concentrate, difficult to remembering or thinking clearly, unsatisfactory work, depression, and difficult to solve problems. The long-term effects such as cardiovascular disease, obesity, and cancer.